A Shaman Drum Hammer from the Medieval City of Turku, Finland - Rainio, Riitta (2016)
In this paper, I analyze and interpret the T-shaped antler artefact that was excavated from the 14th−15th century layers of the city of Turku, Finland. On the basis of the basic form, size, use-wear and raw material, the artefact is a drum hammer of Saami origin. Although the ornaments are uncharacteristic of traditional Saami drum hammers, similar type of motifs can be found in another medieval drum hammer from Norway. In the medieval city of Turku, the drum hammer seems to have been in a use that was different from the original shamanistic one. On the basis of the archaeological context, the drum hammer was hidden in the floor construction of a dwelling house, most probably as a gift to the house spirit or some other kind of transcendent being. As similar deposits of sound-related artefacts and instruments can be found in the later Finnish folklore, it is possible to carry on the reasoning further. The hidden drum hammer can be interpreted as a special sound deposit, by which the drumming sound was transported to the other transcendent reality, where it protected the household in an inaudible way. Peer reviewed